Mapping qualitative research on motor imagery: A scoping review - Juliet M. Rowe; Theresa C. Gaughan; Shaun G. Boe (PLoS ONE, 2026)
Aim To examine the extent to which qualitative methods have been used in motor imagery research, and to characterize how these approaches have been applied. Design Scoping review conducted in accordance with JBI methodology. Methods Eligible articles included peer-reviewed literature investigating motor imagery using qualitative methods. Screening and data extraction were conducted in Covidence. Data were synthesized descriptively and presented in tabular form. Results Thirty-nine articles met the inclusion criteria. Most were situated in sport psychology ( n = 23; 59%), with athletes comprising the most frequently studied population ( n = 20; 51.3%). Over half of the qualitative studies ( n = 20; 51.3%) did not report a specific research design. The predominant focus was on how specific populations use motor imagery ( n = 27; 69.2%), while only one study (2.6%) investigated learning through motor imagery. Conclusion and Impact The literature is heavily weighted toward sport psychology and understanding athletes’ use of imagery, with limited attention to how motor imagery is experienced in experimental settings. Notably, few studies have examined the process of imagery – particularly its role in learning – within laboratory contexts. Given that such laboratory research often forms the foundation for the application of motor imagery in healthcare, including rehabilitation, the absence of qualitative insights into participants’ experiences represents an important gap. Clearer reporting of qualitative designs and more in-depth exploration of motor imagery experiences are needed to ensure that applications, particularly in rehabilitation, are grounded in the perspectives of those engaging in motor imagery practice.